Accounting students’ profile versus academic performance: A five-year analysis - Papageorgiou, E. (South African Journal of Higher Education, 2017)
The purpose of the study was explore first-year accounting students’ profile (N= 3075) in terms of academic performance over a period of five years (2010-2014) at a South African university. The objectives were to determine the impact of students’ profile (age, gender, race) and the students’ pre-university knowledge brought to lectures (language, subject choice, whether Accounting was a Grade 12 subject) on academic performance. A quantitative research method was used. The study concluded that student profile, in particular gender, race and pre-university knowledge of first-year accounting students, does have an impact on the academic performance. Interestingly, for the period 2010 to 2013, no correlations was found between Accounting I students’ academic performance and languages other than English and Afrikaans but in 2014 significant correlations were found between Accounting I students’ academic performance and two first languages; Sepedi and Sesotho. The findings identified trends for at-risk students consequently assisting to implement interventions to assist at-risk students to pass Accounting I. The study’s limitations include, firstly, the use of only one university and, secondly, a sample size including only first-year Accounting students. The value of this study should enable the university to identify students who fit the profile in terms of passing Accounting I in their first year at an academic institution.